Pengaruh keterampilan membaca dan menulis terhadap kemampuan berpidato pembelajar Sekolah Menengah Atas swasta Jakarta Timu - Yayan Sudrajat; Ni Wayan Ayu Permata Sari; Maman Paturahman; Yulia Agustin (SINAU : Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
The purpose of this study was to determine the effect of reading and writing on students' speech abilities. This research was conducted at East Jakarta Private Senior High School. The time of the research was carried out from September to December 2022. The method used in this study was descriptive (expost facto), namely the procedure for solving problems that are currently happening by describing or describing the facts in the field as they really are. The analysis technique used is correlational. These findings indicate that the variable data on reading skills varies quite a bit. The normality test results obtained with the SPSS 17.0 for Windows process variable reading skills (X1) on students' speech abilities (Y) can be seen in the graph or figure 5.4 that the data (dots) spread around the diagonal line and the distri-bution follows the diagonal line which means that regression is feasible to use to predict the reading skill variable (X1) based on the input of the speech ability variable (Y).